Assessment of Chronic Toxicity of an Ayurvedic Herbo-Metallic Formulation Rasaraj Rasa in Wistar Rats - Chaitali S. Waghmare; Shivcharan R. Bidve; Ramacharya V. Gudi; Megha L. Nalawade; Mukesh B. Chawda (Korean Pharmacopuncture Institute, 2022)
Objectives: This study aimed to assess the adverse effects of Rasaraj Rasa tablets after repeated oral administration for 180 days in Wistar rats.Methods: Wistar rats were divided into five groups, of which three were treated with 54, 162, and 270 mg/kg body weight of Rasaraj Rasa, respectively, which correspond to one, three, and five times the proposed human therapeutic dose, for 180 days consecutively. The fifth group (satellite) also received 270 mg/kg body weight of Rasaraj Rasa for 180 days. Body weight and food intake were measured weekly. At the end of the study, all rats were sacrificed, and their blood, serum, and organs were collected and examined using hematology, serum biochemistry, gross pathology, and histopathology tests. In contrast, the satellite group was kept for 4 weeks after treatment.Results: No significant treatment-related toxicological findings were observed in the clinical features, body weight, laboratory findings, and pathological findings of the high-dose treated groups, when compared to those of the control group.Conclusion: The no-observed-adverse-effect-level for Rasaraj Rasa in Wistar rats is set at 270 mg/kg body weight.